SIMULASI PENDETEKSI KELEMBABAN PADA TANAH MENGGUNAKAN SENSOR DHT22 DENGAN PROTEUS - Ahmad Roihan; Aditya Mardiansyah; Adlan Pratama; Akmal Ardhi Pangestu (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2021)
This study aims to provide convenience for farmers and orchid lovers. Because giving water to orchid plants requires special attention if the orchid plant has too much water at the time of watering, the orchid plant cannot grow optimally and vice versa, if the orchid plant at the time of watering, the orchid plant lacks water then the orchid plant does not grow optimally, This tool uses a DHT22 sensor. Answering this problem, the researchers created an automatic orchid sprinkler with a DHT 22 sensor. The DHT22 sensor was chosen over the DHT11 sensor because it has a wide measurement range, namely 0 to 100% for humidity and -40 degrees Celsius to 125 degrees Celsius for temperature. This sensor also has a high-accuracy digital output. DHT 22 requires a supply voltage of 2.4 and 5.5 V. Serial clock input is used to synchronize communication between the microcontroller and DHT22, then it is used to transfer data from and to DHT22. Product trials are carried out to determine the performance of products that have been made and product revisions are made if there are errors, then trial use on orchid plants.